2015
DOI: 10.1051/limn/2015003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the distribution of fish during receding flood in lower Irtysh: effects of water level and diurnal cycle

Abstract: -Subarctic Siberian freshwater ecosystems are unique due to severe climatic conditions and strong seasonal changes of water supply, temperature and nutrient availability. In this work we evaluated the relative influence of the illumination level linked with the diurnal cycle, local environmental heterogeneity and water level changes during the receding flood on the distribution and migrations of fish in the Lower Irtysh basin. The data are based on hydroacoustic surveys conducted from boats in the main channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(74 reference statements)
0
1
0
1
Order By: Relevance
“…During the wintering season, the basic habitat requirements of other species of fish also shift to the most important aspects: sufficient depth and low flow rates (Mochek et al, 2019;Wang et al, 2019). In the study of riverbed depressions, it was shown (Mochek et al, 2015) that aggregations of fish in these water areas are also found during open-water periods. The study (Borisenko et al, 2013) revealed that riverbed depressions mostly form on the vertices of meanders.…”
Section: Discussionmentioning
confidence: 99%
“…During the wintering season, the basic habitat requirements of other species of fish also shift to the most important aspects: sufficient depth and low flow rates (Mochek et al, 2019;Wang et al, 2019). In the study of riverbed depressions, it was shown (Mochek et al, 2015) that aggregations of fish in these water areas are also found during open-water periods. The study (Borisenko et al, 2013) revealed that riverbed depressions mostly form on the vertices of meanders.…”
Section: Discussionmentioning
confidence: 99%
“…Река Иртыш является важной составной частью Обь-Иртышского бассейна, обладая значительными водными биологическими ресурсами, в первую очередь рыбными. Для проведения фундаментальных и прикладных исследований в области ихтиологии в пределах бассейна Иртыша сотрудниками ТКНС УрО РАН и ИПЭЭ им А. Н. Северцова (борисенко и др., , Mochek et al, 2015 используется программно-технический комплекс «AsCor» (производитель ООО «Промгидроакустика», г. Петрозаводск). Данный комплекс предназначен для количественной оценки запасов гидробионтов гидроакустическим методом в реальном и отложенном времени в научных и прикладных рыбохозяйственных работах на внутренних водоемах и прибрежных районах морей.…”
Section: а а чемагинunclassified